2011
DOI: 10.1007/s11269-011-9891-1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Risk Management in Transnational River Basins: The Rhine

Abstract: Climate change is likely to have an impact on the discharge of the European river Rhine. To base adaptation strategies, to deal with these changing river discharges, on the best scientific and technical knowledge, it is important to understand potential climate impacts, as well as the capacity of social and natural systems to adapt. Both are characterized by large uncertainties, at different scales, that range from individual to local to regional to international. This review paper addresses three challenges. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 65 publications
0
24
0
1
Order By: Relevance
“…In a similar fashion, the vulnerability and bottom-up approaches start at the local scale of households and communities to explore what conditions enable successful coping with floods (Wilby and Dessai, 2010). The focus is on the vulnerability and resilience of the risk-related system itself rather than on climate projections (Hall and Murphy, 2011;van Pelt and Swart, 2011) with the aim to develop robust and flexible strategies for dealing with changing floods.…”
Section: Ensemble Spread In Climate Variablesmentioning
confidence: 99%
“…In a similar fashion, the vulnerability and bottom-up approaches start at the local scale of households and communities to explore what conditions enable successful coping with floods (Wilby and Dessai, 2010). The focus is on the vulnerability and resilience of the risk-related system itself rather than on climate projections (Hall and Murphy, 2011;van Pelt and Swart, 2011) with the aim to develop robust and flexible strategies for dealing with changing floods.…”
Section: Ensemble Spread In Climate Variablesmentioning
confidence: 99%
“…However, as the climate communities' understanding of the large scale mechanisms that influence climate has improved, seasonal to inter-annual to decadal climate forecasts have become a real prospect (Goddard et al, 2010), with some regions showing more promise than others. Understandably this has attracted much interest from a range of climate sensitive sectors such that outputs from seasonal climate forecasts (SCF) are beginning to be incorporated into the decision making processes related to managing risk in industries such as water (van Pelt et al, 2011), energy (Troccoli et al, 2010), agriculture (Crane et al, 2010) and insurance. Because of seasonal climate forecasting's rapid development as a science, there have been a number of recent reviews of its nature, current status and prospects (Brunet et al, 2010;Dobles-Reyes et al, 2013;Stockdale et al, 2010).…”
Section: Seasonal Climate Forecastingmentioning
confidence: 99%
“…Secondly, the projected climate change could lead to higher design discharges (Bruggeman et al, 2011), although it is found difficult to discover a trend in discharge data for the Rhine, even if climate change has an effect (Diermanse et al, 2010). Also, it is expected that the Rhine discharge entering the Netherlands reaches its physical maximum at 18 000 m 3 s −1 (Pelt and Swart, 2011). Assuming that the Rhine design discharge will increase to 18 000 m 3 s −1 in 2100, the IJssel design discharge could increase to (0.18 × 18 000 =) 3240 m 3 s −1 .…”
Section: System Robustness Analysis Approachmentioning
confidence: 99%